A High Contrast Tri‐state Fluorescent Switch: Properties and Applications. Issue 22 (20th October 2016) - Su, Xing; Wang, Yi; Fang, Xiaofeng; Zhang, Yu‐Mo; Zhang, Ting; Li, Minjie; Liu, Yifei; Lin, Tingting; Zhang, Sean Xiao‐An
Abstract: A high contrast tri‐state fluorescent switch (FSPTPE) with both emission color change and on/off switching is achieved in a single molecular system by fusing the aggregation‐induced emissive tetraphenylethene (TPE) with a molecular switch of spiropyran (SP). In contrast to most of the reported solid‐state fluorescent switches, FSPTPE only exists in the amorphous phase in the ring‐closed form owing to its highly asymmetric molecular geometry and weak intermolecular interactions, which leads to its grinding‐inert stable cyan emission in the solid state. Such an amorphous phase facilitates the fast response of FSPTPE to acidic gases and induces the structural transition from the ring‐closed form to ring‐open form, accompanied with the "Off" state of the fluorescence. The structural transition leads to a planar molecular conformation and high dipole moment, which further results in strong intermolecular interactions and good crystallinity, so when the acid is added together with a solvent, both the ring‐opening reaction and re‐crystallization can be triggered to result in an orange emissive state. The reversible control between any two of the three states (cyan/orange/dark) can be achieved with acid/base or mechanical force/solvent treatment. Because of the stable initial state and high color contrast (Δ λ =120 nm for cyan/orange switch, dark state Φ F <0.01 %), the fluorescent switch is very promising for applications such as displays, chemical or mechanical sensing, and anti‐counterfeiting. Abstract : One molecule multi emission : A high contrast tri‐state fluorescent switch (FSPTPE) with both emission color change and on/off switching is achieved in a single molecular system. The reversible control between any two of the three states (cyan/orange/dark) can be achieved with acid/base or mechanical force/solvent treatment. The fluorescent switch is very promising for applications of display, chemical or mechanical sensing, and anti‐counterfeiting.